Cognitive and Lifestyle Drivers of Financial Behavior: The Moderating Roles of Locus of Control - Leonardo Davidsi Sipayung; Andhi Febisatria; Eureka Try Zarazwanty R. Laega (Universitas Negeri Makassar, 2026)
This study examines the effect of financial literacy, digital financial literacy, financial attitudes, and hedonistic lifestyle on students’ financial behavior, with locus of control and self-efficacy as moderating variables. A quantitative approach with an explanatory research design was employed, involving 300 students from the Faculty of Social Sciences and Law at the State University of Makassar, selected through purposive sampling. Data were collected through a Likert scale questionnaire and analyzed using Structural Equation Modelling based on Partial Least Squares (SEM-PLS). The research findings indicate that financial literacy and financial attitudes have a significant influence on locus of control and financial behavior. In contrast, digital financial literacy and hedonistic lifestyle do not have a significant effect on either locus of control or financial behavior. Locus of control significantly affects financial behavior and moderates the relationships between financial literacy and financial attitudes on financial behavior. Conversely, self-efficacy does not have a significant impact on financial behavior and does not function as a moderating variable. These findings indicate that internal control is a more efficient psychological mechanism than self-confidence alone in influencing students’ financial behavior. The implications of this research highlight the importance of enhancing financial literacy and attitudes that synergize with the development of self-control in financial education programs at universities.